2002
DOI: 10.1021/jf011588b
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Analysis of the Influence of Pectin, White Syrup, and Citric Acid on Aroma Concentration in the Headspace above Pectin Gels

Abstract: Pectin gels consist of polysaccharide networks surrounded by water. The gel networks can prevent release of aroma molecules from the gel to the gas phase above. In this study static headspace measurements were performed to correlate aroma concentration in the gas phase above pectin gels to different amounts of the gel ingredients. As a consequence, aroma concentration in the headspace in relation to gel texture, as characterized by rheology measurements, was also studied. Aroma concentration in the headspace a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 18 publications
4
23
0
1
Order By: Relevance
“…A HM pectin decreased the release of some aroma compounds when it was applied in a strawberry jam (Guichard, Issanchou, Descourvieres, & Etievant, 1991). This was also confirmed by Hansson, Leufvén, Pehrson, & Stenlöf (2002), who demonstrated that a stronger HM pectin gel led to a lower headspace concentration of aroma compounds, due to their increased entrapment in the gel structure. Studies to determine the relationship between aroma release and sensory perception have mainly been performed on HM pectin gels (Boland, Buhr, Giannouli, & van Ruth, 2004;Boland, Delahunty, & van Ruth, 2006), but the effects of the molecular properties of pectin on the release of aroma compounds and sensory perception within gel systems have rarely been studied.…”
Section: Introductionsupporting
confidence: 56%
“…A HM pectin decreased the release of some aroma compounds when it was applied in a strawberry jam (Guichard, Issanchou, Descourvieres, & Etievant, 1991). This was also confirmed by Hansson, Leufvén, Pehrson, & Stenlöf (2002), who demonstrated that a stronger HM pectin gel led to a lower headspace concentration of aroma compounds, due to their increased entrapment in the gel structure. Studies to determine the relationship between aroma release and sensory perception have mainly been performed on HM pectin gels (Boland, Buhr, Giannouli, & van Ruth, 2004;Boland, Delahunty, & van Ruth, 2006), but the effects of the molecular properties of pectin on the release of aroma compounds and sensory perception within gel systems have rarely been studied.…”
Section: Introductionsupporting
confidence: 56%
“…[7][8][9] Lipids, proteins and carbohydrates result in different degrees of volatile compound interaction, depending on the hydrophobicity of the volatile compound, diffusion and partition coefficient, and rheological properties of the aqueous phase. 10,11 Smaller molecules, such as simple sugars and acids, either adsorb or have a 'salting out' effect on some volatile compounds. 12,13 Phenolic compounds present in wine and some fruit juices undergo chemical complexes with flavour volatiles.…”
Section: Introductionmentioning
confidence: 99%
“…These methods are used for separation, quantification and/or identification of the components, sampling at a fixed time during flavour release [2,3]. This classical methodology allows the accurate analysis of volatile compounds and determines the chemical nature of the components of flavour samples.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the study of the influence of gel structural properties on flavour release is a field of research in continuous progress in food chemistry, as the methods for analyzing rheological properties become accessible [3]. Thus, the aim of the present work is to explore the capabilities of a simple method based on the electronic nose methodology to investigate the kinetics of flavour release of a multi-component essence and the influence of the encapsulation media.…”
Section: Introductionmentioning
confidence: 99%